O recomeçar do novo começo em Com Armas Sonolentas, de Carola Saavedra - (:unkn) unknown (Universidade Federal do Pampa, 2021)
This article presents the possibility of considering a new beginning in the novel Com Armas Sonolentas, by Carola Saavedra. It seeks to contribute to the critical fortune of the work and to promote discussion, on a national level, on the theme of motherhood in its literary perspective, bringing maternity and the new beginning proposed by the author Hannah Arendt to the theme. The methodology used consists of writing the scientific article with a qualitative approach of an explanatory nature, based on bibliographic research, in the analysis of the novel by Carola Saavedra, Com Armas Sonolentas. The research is based on the theme of motherhood, based on the work of Hannah Arendt, Human Condition, in order to present the perspective of the new beginning, in addition to a literature review with authors who address the themes of the aforementioned authors. In this sense, it is maintained that literature is combined with action and the possibility of a new beginning, through it we can listen, dialogue and reflect on the issues of the feminine, on the body, on motherhood and on the mother and daughter relationship. In this way, the restart gives women their own voice, identity, fighting power and visibility to women's issues, including motherhood and its questions.
Keywords: Maternidade; Literatura Feminina; Maternity; Female Literature; CNPQ::LINGUISTICA, LETRAS E ARTES